Principles and Biomedical Applications of Self-Assembled Peptides: Potential Treatment of Type 2 Diabetes Mellitus - Alireza Mohammad Karim (MDPI AG, 2024)
Type 2 diabetes mellitus (T2DM) is the most prevalent metabolic disorder worldwide. There have been tremendous efforts to find a safe and prolonged effective therapy for its treatment. Peptide hormones, from certain organisms in the human body, as the pharmaceutical agents, have shown outstanding profiles of efficacy and safety in plasma glucose regulation. Their therapeutic promises have undergone intensive investigations via examining their physicochemical and pharmacokinetic properties. Their major drawback is their short half-life in vivo. To address this challenge, researchers have recently started to apply the state-of-the-art molecular self-assembly on peptide hormones to form nanofibrillar structures, as a smart nanotherapeutic drug delivery technique, to tremendously enhance their prolonged bioactivity in vivo. This revolutionary therapeutic approach would significantly improve patient compliance. First, this review provides a comprehensive summary on the pathophysiology of T2DM, various efforts to treat this chronic disorder, and the limitations and drawbacks of these treatment approaches. Next, this review lays out detailed insights on various aspects of peptide self-assembly: adverse effects, potential applications in nanobiotechnology, thermodynamics and kinetics of the process, as well as the molecular structures of the self-assembled configurations. Furthermore, this review elucidates the recent efforts on applying reversible human-derived peptide self-assembly to generate highly organized smart nanostructured drug formulations known as nanofibrils to regulate and prolong the bioactivity of the human gut hormone peptides in vivo to treat T2DM. Finally, this review highlights the future research directions to advance the knowledge on the state-of-the-art peptide self-assembly process to apply the revolutionary smart nanotherapeutics for treatment of chronic disorders such as T2DM with highly improved patient compliance.